Research on the impact of live streaming marketing by online influencers on consumer purchasing intentions - Wang, Xueli; Aisihaer, Nadilai; Aihemaiti, Aihetanmujiang (Frontiers in Psychology, 2022)
Drawing from the stimulus-organism-response (S-O-R) model, this paper explores the impact on consumer attitudes in the context of Chinese online influencers' e-commerce live streaming. To examine our hypothesis, we distributed our survey to the Chinese consumers with live streaming shopping experiences. By analyzing data from 430 valid questionnaires, a hierarchical regression analysis was used to examine the hypotheses. The results show that the expertise, bargaining power, after-sales services, and live streaming schedules of online influencers affect consumer trust in online influencers. The expertise, bargaining power and livestreaming schedules of online influencers affect consumer impulsivity. Moreover, the trust and impulsiveness of online influencers increases consumers' purchasing intentions. The implications and future research directions are discussed.S